2019
DOI: 10.1002/ange.201901386
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Synthetic Route to Cycloheximide and Analogues That Potently Inhibit Translation Elongation

Abstract: Cycloheximide (CHX) is an inhibitor of eukaryotic translation elongation that has played an essential role in the study of protein synthesis. Despite its ubiquity, few studies have been directed towards accessing synthetic CHX derivatives, even though such efforts may lead to protein synthesis inhibitors with improved or alternate properties. Described here is the total synthesis of CHX and analogues, and the establishment of structure–activity relationships (SAR) responsible for translation inhibition. The SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We then sought to explore how Reg3g level could be regulated by tacrolimus. Cycloheximide a protein synthesis inhibitor (Park et al, 2019) was applied to determine whether the degradation of Reg3g protein was impacted by tacrolimus. Interestingly, the time‐course analysis showed that tacrolimus treatment did not result in detectable changes in the degradation rate of Reg3g protein (Figure S2), thereby suggesting that tacrolimus might not reduce Reg3g level by causing protein degradation.…”
Section: Resultsmentioning
confidence: 99%
“…We then sought to explore how Reg3g level could be regulated by tacrolimus. Cycloheximide a protein synthesis inhibitor (Park et al, 2019) was applied to determine whether the degradation of Reg3g protein was impacted by tacrolimus. Interestingly, the time‐course analysis showed that tacrolimus treatment did not result in detectable changes in the degradation rate of Reg3g protein (Figure S2), thereby suggesting that tacrolimus might not reduce Reg3g level by causing protein degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Cycloheximide (CHX) is a commonly used protein synthesis inhibitor [29] and a CHX‐chase assay was conducted using CHX (Sigma, USA). After the si‐MEG3 was transfected into BV2 cells, the cells were mixed with 20 μg/ml CHX and the protein level of HuR was measured via Western blot at 0, 10, 20, and 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by these questions, we completed a total synthesis of CHX that enabled identification of analogs with increased potencies, including benzylester 2 and N -hydroxysuccinimide ester 3 (Figure A) . The relative stereochemistry of the C13-methyl group was essential for the enhanced inhibitory activity of the C13-modified derivatives.…”
mentioning
confidence: 99%
“…The amino group was then acylated through peptide coupling with various carboxylic acids to afford CHX C13-amide derivatives. Many of these amide derivatives were effective translation inhibitors, as assessed by a cellular assay for translation that measures incorporation of 2′- O -propargyl puromycin (OPP) (Figure B). , In particular, this includes benzamide 8 (IC 50 = 63 ± 4.5 nM), which is approximately 40 times more active than CHX (Figure C). Derivatives containing simple modifications to the benzamide were not as effective (Figure B).…”
mentioning
confidence: 99%
See 1 more Smart Citation